Bronchobiliary fistula from foreign body reaction or cholelithiasis. Issue 1 (February 2014) - Jin, Xiaotai; Yi, Lin; Lin, Andy; Yao, Yongliang; Yang, Weiping; Chu, Peiguo G.; Yen, Christina; Qiu, Weihua
<x xml:space="preserve">Abstract</x> Bronchobiliary fistula (BBF) is an abnormality between the bronchial tree and biliary tract system. Misdiagnosis and delayed treatment might have a high mortality rate. Although some characteristics relevant to BBF have been introduced, difficulties and controversies in diagnosis and treatment need further investigation. In the present study, we summarize the diagnostic and surgical treatment experience of a 65‐year‐old male patient who presented with an irritating cough and biliptysis. As he had a history of aortic valve replacement surgery and schistosomial cirrhosis, the provisional diagnosis was BBF, which might be secondary to a foreign body reaction or liver cirrhosis and chronic cholecystitis and cholelithiasis. During the surgery, it was discovered that the right lobe of the liver was significantly atrophied with irregular contours, and the gallbladder was adjacent to the diaphragm with a fistula between the fundus of the gallbladder and the right semidiaphragm. These results confirmed that the BBF in this patient resulted from cholelithiasis associated with serious schistosomial cirrhosis. He was successfully treated with a right hepatic lobe resection and Roux‐en‐Y hepaticojejunostomy. The diaphragm defect was repaired by imbrication of the repaired liver and lower lobe's edges. A high index of clinical suspicion can be generated by patients who present with recurring irritating cough and production of bile‐like sputum. The manifestations and responses to conservative treatment are crucial in clinical judgment, and surgical intervention is the primary treatment choice when other approaches have failed or there are complications from the underlying disease.